Receptive Skill in Reading Correlates with Students' Writing Competence - Napigkit, Chorla; Rodriguez, Elmira (JPAIR Institutional Research, 2017)
A good reading comprehension could result to a better writing competence. However, a number of the Bachelor of Elementary Education students of Jose Rizal Memorial State University - Tampilisan Campus were observed to be a bit weak in the use of receptive and productive skills as evidenced by their responses in the teaching-learning situations. The study assessed the level of the receptive and productive skills of the 1st year BEEd students of JRMSU-TC, S.Y. 2012-2013. The study used the descriptive-evaluative method to determine the level of the receptive skills, namely, listening and reading comprehension, and productive skills, namely, speaking and writing competencies. The researchers conducted a test on the subjects using test questionnaires, picture cues, and composition writing. Using frequency counting, percentage, weighted mean and multiple regression analysis, the study revealed that majority of the subjects is "good" in their productive skills such as speaking and writing competencies. The students' receptive skills, particularly in reading comprehension significantly relate to their writing ability, but there is an insignificant relationship between reading and speaking as well as in listening comprehension that negates their speaking and writing competencies. Therefore, a significant association exists between reading and writing, but there is no significant relationship between listening and speaking as well as into writing.
Keywords: Language and Communication; receptive and productive skills; descriptive-evaluative method